(untitled) (GESTIÓN Y TENDENCIAS, 2024)
The article discusses the importance of organizational resources and capabilities in strategic business management. From the Resource-Based View (RBV) of the firm, the paper analyzes how companies achieve and sustain competitive advantages through their unique resources and capabilities. It emphasizes the distinction between resources and capabilities, highlighting how they shape value creation and competitive advantage. The article also addresses operational and dynamic capabilities, distinguishing between current processes and adaptation to changes in the business environment. Practical examples are included to illustrate the application of these concepts in the real world. This study contributes to understanding how firms can develop effective strategies based on their unique resources and capabilities.